Comparison of histopathological features of pancreatic carcinoma and type 1 autoimmune pancreatitis. (February 2014) - Uehara, Takeshi; Hamano, Hideaki; Kawa, Shigeyuki; Kobayashi, Yukihiro; Yoshizawa, Akihiko; Oki, Keiko; Nakata, Rie; Kobayashi, Akira; Sano, Kenji; Ota, Hiroyoshi
<x xml:space="preserve">Abstract</x> Type 1 autoimmune pancreatitis (AIP‐1) is an immunoglobulin G (IgG)‐4‐related disease (IgG4‐RD), characterized by elevated serum immunoglobulin G4 (IgG4) and infiltration by IgG4+ plasma cells. Pancreatic carcinoma (PC) sometimes shows infiltration by IgG4+ plasma cells, but details have been unclear. We compared pathological findings and expression of IgG4 and IgG in fibroses in 18 PC patients to those from 9 AIP‐1 patients. Fibroses were divided into areas of ductal adenocarcinoma (DA) and obstructive pancreatitis (OP). Serum IgG4 levels were lower than the cut‐off value in all PC patients with no IgG4‐RD. Diffuse lymphoplasmacytic infiltration and eosinophil infiltration were characteristic of fibroses in PC. Though AIP‐1 samples often had storiform fibrosis even in biopsies, PC did not show storiform fibrosis. Ratios of IgG4+ plasma cells/IgG+ plasma cells (IgG4/IgG ratios) in DA and OP were significantly lower than in AIP‐1. However, high‐density IgG4+ plasma cell foci were detected in PC fibroses, particularly around peripheral nerves, vessels, and lymphoid follicles; between lobules and invasion fronts; and within neutrophilic abscesses. In conclusion, the IgG4/IgG ratio is useful in distinguishing PC from AIP‐1, and should be evaluated in three or more areas, as PC can show localized high‐density IgG4+ plasma cell areas.